Saccharomyces cerevisiae’s Potential Application in Improving Quality of Yogurt Produced in Suboptimal Fermentation Conditions - Sukmana, Andreas Binar Aji; Kristiani, Elizabeth Betty Elok; Wicaksono, Rifky Adi (Al-Kauniyah: Jurnal Biologi, 2025)
The quality of a yogurt highly depends on the milk’s quality, the culture, and the incubation temperature. However, many home yogurt makers do not have access to fresh milk and incubator which may lead to subpar-quality yogurt. This research explored the potential of using Saccharomyces cerevisiae to improve yogurt quality when fermentation conditions are suboptimal. The experiment was conducted by inoculating ultra-high temperature (UHT)--sterilized milk with a 10% yogurt starter containing Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus, also various S. cerevisiae concentrations (0; 0.156; 0.625; 2.5; and 10%). The inoculated milk was fermented at 30 °C for 24 hours. Their sensory qualities were examined by the panelists. Their acidity, pH, and microorganism count were examined before and after incubation. S. cerevisiae addition at 2.5% displayed better taste and texture without discernable unpleasant aroma. These improvements might be due to the ethanol production by S. cerevisiae. S. cerevisiae addition was also found to slightly inhibit the growth of L. delbrueckii subsp. bulgaricus and S. thermophilus. However, the combined number of these probiotic microorganisms (2.7 × 108 CFU/mL) was still by the national standard.  S. cerevisiae addition potentially improves yogurt quality made from UHT milk incubated at lower temperatures.